F3. CHILDHOOD MALTREATMENT AND POLYGENIC RISK IN BIPOLAR DISORDERS. (9th April 2019) - Aas, Monica; Bellivier, Frank; Bettella, Francesco; Henry, Chantal; Gard, Sebastien; Kahn, Jean-Pierre; Lagerberg, Trine V; Aminoff, Sofie R; Melle, Ingrid; Leboyer, Marion; Jamain, Stéphane; Andreassen, Ole A; et al.
Abstract: Background: Childhood maltreatment is a well-known risk factor for developing a more severe and complex form of bipolar disorders (BD). However, knowledge is scarce about the interactions between childhood maltreatment and underlying genetic vulnerability on the clinical expression of BD. Methods: We assigned a BD-polygenic risk score (BD-PRS), calculated from the Psychiatric Genomics Consortium, to each individual in a sample of 397 cases with BD. The lifetime clinical expression of BD was characterized using structured interviews and patients completed the Childhood Trauma Questionnaire (CTQ) to assess the severity of Childhood maltreatment. Results: Cases who reported more severe childhood maltreatment had a lower BD-PRS (rho=-0.10, p=0.04). An interaction was observed between BD-PRS and childhood maltreatment on number of mood episodes (p=0.056), whereby low BD-PRS and no childhood maltreatment was associated with having fewer mood episodes (p=0.003). This result was mainly due to an interaction between BD-PRS and childhood maltreatment on major depressive episodes (p=0.01), but not on manic episodes. An interaction between BD-PRS and childhood maltreatment was also identified on the risk of rapid cycling (p=0.0097). No further interactions between BD-PRS and childhood maltreatment were observed for other clinical characteristics (age at onset, suicide attempts, mixed episodes, substance use disorders and psychotic symptoms). Discussion: Less genetic risk may be needed to develop a severe form of BD when exposed to childhood maltreatment, in particular when considering number of major mood episodes and rapid cycling.